MENINGKATKAN KEMAMPUAN MENGENAL HURUF HIJAIYAH ANAK MELALUI PERMAINAN KARTU HURUF DI TKIT AN-NUR WALIKUKUN KABUPATEN NGAWI - Saputra, Alan Lutfi Gesang; Sriyanto, Agus; Ningtyas, Yeni Kusuma (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
This study is based on a lack of understanding of the ability to detect hijaiyah letters in early childhood education. Letter card media is used to aid in the attainment of educational objectives as well as to pique children's interest in learning. At TKIT An-Nur Walikukun, Ngawi Regency, this study aims to determine attempts to improve children's capacity to recognize hijaiyah letters by playing letter cards in group A2. This is a qualitative research method, in which data is collected. In-depth interviews, observational methods, and recording papers or archives are all used by the author. Data reduction, data assessment, and conclusion drawing are the stages done. This is a qualitative descriptive study.